Preliminary Evaluation of a Novel Point of Care Diagnostic Device for Sports-Related Concussion. Issue 6 (6th November 2022) - Wu, Yueming; Abner, Erin L.; Conley, Caitlin; Smoot, M. Kyle; Hosey, Robert; Kaiser, Kim; Lovell, Mark A.
Abstract : Objective: Visinin-like protein 1 (VILIP-1) is a neuron-specific calcium sensor protein rapidly released into blood after mild traumatic brain injury (mTBI) and may be a suitable biomarker for identification of sports-related concussion (SRC). The objective of the study is to test if quantification of a specific post-translationally modified (ubiquitinated) form of VILIP-1 (ubVILIP-1) from a fingerstick blood sample using a point of care (POC) lateral flow device (LFD) can be used to rapidly identify athletes with SRC. Design: Prospective cohort study. Setting: Side-line blood collection at football, soccer, and volleyball games/practices. Participants: Division I athletes with/without SRC. Main Outcome Measures: Blood ubVILIP-1 concentrations. Results: Data collected over 2 athletic seasons from non-SRC athletes (controls) show a small but statistically significant elevation of ubVILIP-1 over an individual season for male athletes ( P = 0.02) dependent on sport ( P = 0.014) and no significant changes in ubVILIP-1 levels between seasons. For SRC athletes, the data show ubVILIP-1 levels substantially increase above baseline as soon as 30 minutes postdiagnosis with peak concentrations and times postinjury that vary based on injury severity. Conclusion: Results of the study suggest quantification of blood ubVILIP-1 levels measured using an LFD may provide an objective identification of athletes with SRC, setting the stage for further study with a larger number of SRC patients.